Réponses

2013-10-25T20:40:48+02:00
1) (x-2)(x+3)-(x-2)(3x+8)
   x²+3x-2x-6-(3x²+8x-6x-16)
   x²+3x-2x-6-3x²-8x+6x+16
   -2x²-x+10
2) (x-2)(x+3)-(3x+8)
     (x-2)(x+3-3x-8)
     (x-2)(-2x-5)
3) x=2
   (2-2)(2+3)-(2-2)(6+8)
   0-0=0
   x=5
   (5-2)(5+3)-(5-2)(15+8)
   (3)(8)-(3)(23)
   24-69=-45
4) x=-5/2
   (-5/2-2)(-5/2+3)-(-5/2-2)(-15/2+8)
   (-9/2)(1/2)-(-9/2)(1/2)
   (-9/4)-(-9/4)
   -9/4+9/4=0
A(x)=0
(x-2)(x+3)-(x-2)(3x+8)=0
x²+3x-2x-6-(3x²+8x-6x-16)=0
x²+3x-2x-6-3x²-8x+6x+16=0
-2x²-x+10=0

2013-10-25T20:41:54+02:00
A(x)=(x-2)(x+3)-(x-2)(3x+8)        

1) Développer et réduire A(x)
A(x)=(x-2)(x+3)-(x-2)(3x+8)
=x²+3x-2x-6-(3x²+8x-6x-16)
=x²+x-6-3x²-8x+6x+16
=-2x²-x+10

2) Factoriser A(x)
(x-2)(x+3-3x-8)
=(x-2)(-2x-5)

3) Calculer A(x)
pour x=2
-2*2²-2+10=-2*4-2+10=-8-2+10=0

et pour x=5
-2*5²-5+10=-50-5+10=-55+10=-45

4) Calculer A(x)pour x=-5/2 ; 
-2(-5/2)²-(-5/2)+10=-2*25/4+5/2+10=-50/4+10/4+40/4=0

Résoudre A(x)=0
=x²+3x-2x-6-(3x²+8x-6x-16)
=x²+x-6-3x²-8x+6x+16
=-2x²-x+10